Comparing delivery channels to promote nutrition-sensitive agriculture: A cluster-randomized controlled trial in Bangladesh - Ahmed, Akhter; Coleman, Fiona M.; Hoddinott, John F.; Menon, Purnima; Parvin, Aklima; Pereira, Audrey; Quisumbing, Agnes R.; Roy, Shalini (International Food Policy Research Institute, 2022)
We use a randomized controlled trial in rural Bangladesh to compare two models of delivering nutrition content jointly to husbands and wives: deploying female nutrition workers versus mostly male agriculture extension workers. Both approaches increased nutrition knowledge of men and women, household and individual diet quality, and women’s empowerment. Intervention effects on agriculture and nutrition knowledge, agricultural production diversity, dietary diversity, women’s empowerment, and gender parity do not significantly differ between models where nutrition workers versus agriculture extension workers provide the training. The exception is in an attitudes score, where results indicate same-sex agents may affect scores differently than opposite-sex agents. Our results suggest opposite-sex agents may not necessarily be less effective in providing training. In South Asia, where agricultural extension systems and the pipeline to those systems are male-dominated, training men to deliver nutrition messages may offer a temporary solution to the shortage of female extension workers and offer opportunities to scale promote nutrition-sensitive agriculture.